Fate and effects of heavy metals on the Arkansas River - Clements, W. H. (William H.), author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1991)
This research examined fate and effects of heavy metals (Cd, Cu, Zn) in the Arkansas River, a Colorado stream receiving metals form historic mining operations. Benthic invertebrate communities were sampled at several stations located upstream and downstream form California Gulch, a U.S. EPA "Superfund" site in Leadville, CO. Impacted stations were characterized by reduced species richness, reduced abundance, and a shift in community composition from metal-sensitive taxa (e.g. Ephemeroptera) to metal-tolerant taxa (Orthocladiini chironomids and Trichoptera).
Completion Report No. 163.
15 December, 1991.
Keywords: Heavy metals -- Environmental aspects; Copper -- Bioaccumulation; Aquatic organisms -- Effect of heavy metals on; Cadmium -- Environmental aspects; Zinc -- Environmental aspects; Arkansas River; California Gulch (Lake County, Colo.)